Prinsip Kesantunan dalam Acara Sombah Nasi Pernikahan Adat Masyarakat Melayu Kenegerian Siberakun Kecamatan Benai Kabupaten Kuantan Singingi - Kurniawan, Wahyu; Hermaliza (UIR PRESS, 2021)
Humans in speaking really need to pay attention to politeness when interacting or communicating with other humans, the goal is that humans can use polite speech and do not make mistakes when speaking or communicating. So with that, politeness is needed and very much needed. Often we hear the conversation of people in a certain area who express impolite words. Limited to one problem. The problem of this research is how the principle of politeness in the Sombah Nasi ceremony, the Traditional Marriage of the Kenegrian Siberakun Community, Benai District, Kuantan Singingi Regency. The purpose of this study is to describe, analyze, interpret, and conclude the Malay language politeness maxim in the traditional marriage sombah rice of the Kenegrian Siberakun Community, Benai District, Kuantan Singingi Regency. In this study, the researcher uses Leech's politeness principle because until now it is still used and is the most complete and relatively comprehensive according to Leech (Rahardi, 2005: 59) there are six maxims of politeness principles. This study uses a qualitative descriptive method because the data analyzed is not to accept or reject the hypothesis (if any), but the results of this analysis are descriptive of the observed symptoms. The techniques used are recording techniques, listening techniques and note-taking techniques. The conclusion of this study is the politeness maxim in the Sombah Nasi ceremony, the Malay Traditional Marriage of the Kenegrian Siberakun Community, Benai District, Kuantan Singingi Regency. Based on the research results of the politeness maxim in the Sombah Nasi ceremony, the Malay Traditional Marriage of the Kenegrian Siberakun Community, Benai District, Kuntang Singingi Regency, the most spoken utterances amounted to 16 utterances. The politeness maxim which contains the maxim of wisdom is 10 utterances. The politeness maxim which contains the maxim of generosity is 10 utterances. The politeness maxim which contains the meaning of the maxim of praise is 10 utterances. The politeness maxim which contains the meaning of the maxim of simplicity is 10 utterances. consensus is 16 utterances. The maxim of politeness which contains the meaning of the maxim of sympathy is 9 utterances.